2008
DOI: 10.1037/1076-8971.14.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Gold versus platinum: Do jurors recognize the superiority and limitations of DNA evidence compared to other types of forensic evidence?

Abstract: In a series of studies, the authors examined (a) public perceptions concerning forensic scientific evidence, (b) the relative influence attributed to DNA evidence compared to other forms of forensic identification evidence, and (c) the impact of cross-examination addressing the limitations of DNA testimony. In Studies 1 and 2, both undergraduate students and representative jurors rated DNA as the most accurate and persuasive type of evidence compared to other types of forensic evidence. This finding was consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(145 citation statements)
references
References 48 publications
10
134
0
1
Order By: Relevance
“…Because DNA evidence has tremendous credibility (Lieberman, Carrell, Miethe, & Krauss, 2008), whereas shoeprint comparison is less well known, we also expect (Hypothesis 3) that DNA evidence will produce larger shifts in estimates of the chances of guilt than shoeprint evidence even when the statistics that the expert uses to characterize the strength of the evidence are the same. And because the log scale may make it easier to express high and low values and thereby facilitate shifts in judgment in response to the forensic evidence, we expect (Hypothesis 4) that people's judgments will be more responsive to forensic science evidence (greater shifts in estimated chances of guilt), when these judgments are elicited on the log scale than when elicited as statements of odds.…”
Section: Logical Coherencementioning
confidence: 99%
“…Because DNA evidence has tremendous credibility (Lieberman, Carrell, Miethe, & Krauss, 2008), whereas shoeprint comparison is less well known, we also expect (Hypothesis 3) that DNA evidence will produce larger shifts in estimates of the chances of guilt than shoeprint evidence even when the statistics that the expert uses to characterize the strength of the evidence are the same. And because the log scale may make it easier to express high and low values and thereby facilitate shifts in judgment in response to the forensic evidence, we expect (Hypothesis 4) that people's judgments will be more responsive to forensic science evidence (greater shifts in estimated chances of guilt), when these judgments are elicited on the log scale than when elicited as statements of odds.…”
Section: Logical Coherencementioning
confidence: 99%
“…192-212). The calculation and reporting of statistical probabilities frequently are controversial (Kaye, 2009;Perlin, Kadane & Cotton, 2009;Thompson, 2009) and can be misunderstood by juries (Lieberman, Miethe, Carrell, & Krauss, 2008). In short, "DNA analysis does not and cannot answer questions of guilt or innocence with epistemological certainty" (Aronson & Cole, 2009, p. 627).…”
Section: Us Supreme Court Justice Antonin Scalia Has Offered a Similamentioning
confidence: 98%
“…Compared with other types of scientific evidence, research has consistently found DNA to be the most authoritative evidence type for mock-jurors, and DNA has been associated with more guilty verdicts than fingerprint or hair evidence (Lieberman et al, 2008). DNA may be considered the gold standard of scientific evidence, and common media representations of its credibility may bias perceptions of its value.…”
mentioning
confidence: 98%
“…They found that both strong and weak physical evidence was more influential than strong and weak EWT. In addition, Lieberman, Carrell, Miethe, and Krauss (2008) compared the contribution of various evidence types including DNA, fingerprints and EWT to mock-juror verdicts. Across two crimes, DNA was found to be the most influential and EWT the least.…”
mentioning
confidence: 99%